RFID Opportunity Analysis Toolset for Lean Manufacturing - Brintrup, A; Ranasinghe, D; McFarlane, D (2010)
Although RFID is seen by many as a revolutionary enabler of automated data capture, confusion still remains as to how manufacturing organisations can identify cost-effective opportunities for its use. Managers view promotional business case estimates as unjustified, simulation based analysis and analytical models as secondary modes of analysis, and case studies are scarce. Further, there is a lack of simple tools to understand how RFID can help to achieve a leaner manufacturing environment, after the use of which practitioners can be routed to grounded forms of analysis. The purpose of this paper is to provide and test such a toolset, which uses the seven Toyota Production System wastes as a template. In our approach, RFID technology is viewed as a vehicle to achieve leaner manufacturing through automated data collection, assurance of data dependencies, and improvements in production and inventory visibility. The toolset is tested on case examples from two push-based, multi-national fast moving consumer goods manufacturing companies. The opportunity analysis is shown to identify not only initially suspected areas of improvement, but also other areas of value.